2008
DOI: 10.1007/s00018-008-8495-2
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous retroviruses

Abstract: Endogenous retroviruses (ERVs) most likely are remnants of ancient retroviral infections. ERVs preserve functions of exogenous retroviruses to a varying extent, and can be parasites, symbionts or more or less neutral genetic 'junk'.Their evolution has two facets, pre- and post-endogenization. Although the two are not clearly separated, the first pertains to retroviral evolution in general and the second to the fate of repetitive DNA and the evolution of the host organism and its genome. The study of ERVs provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
64
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(68 citation statements)
references
References 74 publications
4
64
0
Order By: Relevance
“…Numerous studies have found that the placenta is generally permissive to transcription initiating from LTRs, and some ERV copies are expressed at higher levels in placenta than other tissues (4,10,11). In fact, ERVs may have been central in the evolution of placental mammals, and domestication of ERV proteins has led to their serving important functions in this tissue (12)(13)(14).…”
mentioning
confidence: 99%
“…Numerous studies have found that the placenta is generally permissive to transcription initiating from LTRs, and some ERV copies are expressed at higher levels in placenta than other tissues (4,10,11). In fact, ERVs may have been central in the evolution of placental mammals, and domestication of ERV proteins has led to their serving important functions in this tissue (12)(13)(14).…”
mentioning
confidence: 99%
“…Interestingly, the SASPase gene is only found in the mammalian genome. Although it has not been proven that the SASPase gene in mammals is derived from an ancient retroviral infection into the germline, this molecular mechanism would be the fi rst example of a virus-related element that has contributed to the evolution of vertebrate skin [ 7,70 ] . Therefore, the study of the SASPase physiological function should provide valuable clues that reveal the role of the SC in mammals and how they adapted to life on land.…”
Section: Origin Of Saspase and Adaptation To Life On Landmentioning
confidence: 98%
“…HERVs posses a single open reading frame containing the genes gag, pol and env, which are Xanked by LTRs at the 5Ј and 3Ј ends [5,6]. For the most part, the interplay between mutations [3], epigenetic mechanisms and posttranscriptional regulations silence HERV expression [2,7]. Yet, there are some examples of HERVs executing preserved functions as do the proviruses of their exogenous ancestors, making them something between parasites and symbionts.…”
Section: Introductionmentioning
confidence: 98%
“…The process of endogenization is dependant on the viruses' ability to withstand restrictions common to all cells, their potential to infect reproductive tissues, that is, cells of the germ line and Wnally to proceed to Wxation in the human genome. All these processes must happen without loss of Wtness of the host, thus excluding highly pathogenic ERV [2]. Generally, HERVs are classiWed into three groups: class I (gamma (like) retroviruses), class II (beta (like) retroviruses) and class III (spuma (like) retroviruses) [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation